2022
DOI: 10.3390/molecules27020503
|View full text |Cite
|
Sign up to set email alerts
|

Production of COx-Free Hydrogen and Few-Layer Graphene Nanoplatelets by Catalytic Decomposition of Methane over Ni-Lignin-Derived Nanoparticles

Abstract: Nickel (Ni)-lignin nanocomposites were synthesized from nickel nitrate and kraft lignin then catalytically graphitized to few-layer graphene-encapsulated nickel nanoparticles (Ni@G). Ni@G nanoparticles were used for catalytic decomposition of methane (CDM) to produce COx-free hydrogen and graphene nanoplatelets. Ni@G showed high catalytic activity for methane decomposition at temperatures of 800 to 900 °C and exhibited long-term stability of 600 min time-on-stream (TOS) without apparent deactivation. The catal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
(41 reference statements)
0
4
0
Order By: Relevance
“…However, when exposed to the Ni core, the deposited graphene cells over Ni@G NPs act as active sites for the continuous decomposition of CH 4 . [51] The dark co-fermentation of glucose (C 6 H 12 O 6 ) and surplus algal biomass by Fe 3 O 4 NPs leads to higher H 2 production rates. The work of Srivastav and coworkers described that rate of H 2 synthesis increases 37% higher while using 7.5 mg/L of Fe 3 O 4 NPs.…”
Section: Materials For Hydrogen Evolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, when exposed to the Ni core, the deposited graphene cells over Ni@G NPs act as active sites for the continuous decomposition of CH 4 . [51] The dark co-fermentation of glucose (C 6 H 12 O 6 ) and surplus algal biomass by Fe 3 O 4 NPs leads to higher H 2 production rates. The work of Srivastav and coworkers described that rate of H 2 synthesis increases 37% higher while using 7.5 mg/L of Fe 3 O 4 NPs.…”
Section: Materials For Hydrogen Evolutionmentioning
confidence: 99%
“…The synthesized NCs were significantly used for the catalytic decomposition of CH 4 at 800–900 °C to yield H 2 and graphene nanoplates. However, when exposed to the Ni core, the deposited graphene cells over Ni@G NPs act as active sites for the continuous decomposition of CH 4 [51] …”
Section: Materials For Hydrogen Evolutionmentioning
confidence: 99%
“…25,26 However, studies employing metallic catalysts supported on non-oxides, such as commercial carbonaceous materials (carbon nanotubes (CNTs), activated carbon and carbon black) or obtained from renewable natural sources such as lignocellulosic biomass, are reported in the literature. [27][28][29] Esmizadeh et al 30 reported that catalysts with 25% Fe/ montmorillonite were used for the growth of carbon nanotubes through the deposition of chemical methane vapor. This study shows that the type of organo-modification of the clay before the insertion of Fe affected the purity, diameter, length and yield of the carbon nanotubes formed.…”
Section: Introductionmentioning
confidence: 99%
“…This material can be used for the synthesis of refractory compounds [33][34][35], as a filler for conductive epoxy composites [36], such as electrode for supercapacitors [37], and catalyst for the selective oxidation of H 2 S to sulfur [32,38] etc. Since the synthesis method of CNFs is an attractive CO x -free process [29,39,40] that may be applied to produce both hydrogen and carbon nanomaterials, the important task is to find the application of latter. One of the novel applications of the granulated CNF material for gas sensors was not yet investigated.…”
Section: Introductionmentioning
confidence: 99%